Introducing nanoscaled surface morphology and percolation barrier network into mesoporous silica coatings. Issue 74 (13th August 2015) - Albert, E.; Basa, P.; Deák, A.; Németh, A.; Osváth, Z.; Sáfrán, G.; Zolnai, Z.; Hórvölgyi, Z.; Nagy, N.
<x xml:space="preserve">Abstract</x> The advantages of surface pattern and mesoporous character of silica thin films were combined, while preserving the interconnected pore system or creating laterally separated porous volumes surrounded by nonpermeable compact zones.